Peran Strategi Scaffolding dalam Meningkatkan Efektivitas Evaluasi Pembelajaran Pendidikan Jasmani pada Anak Usia Dini - MIFTACHUS SHOLIKAH (Institut Agama Islam Pangeran Diponegoro Nganjuk, 2026)
Evaluation is an essential component of the learning process, particularly in early childhood education, as it provides information regarding children’s developmental progress and learning achievements. In the context of physical education, evaluation is crucial for assessing the development of motor, cognitive, and social skills among young learners. This study aims to analyze the implementation of scaffolding as an evaluation strategy in physical education learning at TK Murni Asih and to examine its effectiveness in supporting children’s learning outcomes. The research employed a descriptive qualitative approach to explore the application of scaffolding strategies within the learning and evaluation process. Data were collected through observations, interviews, and documentation related to physical education activities. The findings indicate that scaffolding serves as an effective pedagogical strategy by providing structured and gradual assistance that enables children to perform tasks beyond their initial capabilities and progressively achieve greater independence. Through this approach, children demonstrate improvements in motor coordination, social interaction, problem-solving abilities, and learning engagement. Furthermore, the use of scaffolding-based evaluation allows teachers to monitor children’s developmental progress more comprehensively and provide appropriate support according to individual learning needs. The study concludes that scaffolding can be effectively integrated into physical education evaluation practices and has the potential to enhance the quality of learning in early childhood education settings. Keywords: Scaffolding, Learning Evaluation, Physical Education, Early Childhood Education, Learning Outcomes..